Parathyroid hormone in situ measurement in patients with hyperparathyroidism: single-centre experience of 179 patients. Issue 4 (8th March 2022) - Richa, Carine; Haidar, Hazar; Dupeux, Margot; Papon, Jean-François; Lambert, Benoit; Salenave, Sylvie; Bouyacoub, Mohammed; Young, Jacques; Chanson, Philippe; Trabado, Séverine; Maione, Luigi
Abstract: Context: The measurement of parathyroid hormone(PTH) in situ (PTHis) by fine-needle aspiration (FNA) has been proposed as a tool to preoperatively help localize parathyroid glands detected on ultrasound. However, the accuracy of PTHis is highly variable according to the few available studies. Aim: We aimed to develop and validate the PTHis procedure and assessed the performance of PTHis in a large series of patients with hyperparathyroidism and/or undetermined cervical lesions. Patients and methods: The technique set-up consisted of PTHis measurement in thyroid samples from patients with thyroid nodules and patients with high circulating PTH levels (tertiary hyperparathyroidism). Consecutive patients were recruited at one tertiary referral centre from 2017 to 2020 and submitted to ultrasound-guided FNA-PTHis determination. Results: During the method set-up, we obtained undetectable PTHis levels in all non-parathyroid tissues after sample dilutions. PTHis was higher in patients with hyperparathyroidism ( n = 145; 1817 ± 3739 ng/L; range: <4.6–31 140) than in those with thyroid or undetermined cervical lesions ( n = 34; <4.6 ng/mL; P < 0.0001). When evaluating PTHis performance in histologically proven samples (158 lesions from 121 patients), PTHis was detectable in 85/97 parathyroid lesions (87%; range: 22–31;140 ng/L) and undetectable in all non-parathyroid lesions ( n = 61; P < 0.0001). The specificity and positive predictive value were 100%, and the sensitivity was 87.6%. False-negative lesions ( n = 12) were smaller (9.4 ± 5.9 mm) and more often consisted of hyperplasias (75%) than true-positive lesions (16.1 ± 8.4 mm and 33%, P = 0.009 and P = 0.0089, respectively). The method was safe and well tolerated. Four educational cases are also provided. Conclusions: PTHis determination is a safe and well-tolerated procedure that enhances the specificity of ultrasound-detected lesions. If accurately set-up, it confirms the parathyroid origin of uncharacterized cervical lesions.